PENGARUH PENGELOLAAN TUTORIAL ONLINE TERHADAP PARTISIPASI MAHASISWA - Yulia Budiwati (Jurnal Pendidikan Terbuka Dan Jarak Jauh, 2007)
Online tutorial for post graduate Universitas Terbuka students is compulsory. However, data from the report on the online tutorial activities show that student participation rate was low. This article presents a research result that shows the relationship between management factor and students’ participation in the online tutorials. This study used descriptive qualitative approach. The informans were the coordinator of the online tutorial and the Master Program students in the Public Administration Universitas Terbuka. Data were collected through interviews, questionnaires, and observation. The result showed that the quality of management and tutor, the component of discussion score in the tutorial online, and the obstraction in the network had an impact on students’ participation rate in the online tutorials.